Simple Synthesis of 4A Zeolite with the Addition of Al2O3 and Na2EDTA Compounds - Dawolo, Januari; Telaumbanua, Putra Hidayat; O. Laia; N. K. Lase (BRIN Publishing (Penerbit BRIN), 2025)
4A zeolite complex derived from coal has been successfully synthesized through the preparation of fractionated samples, analyzed using atomic absorption spectrophotometry (AAS), resulting in a chemical composition of silica (SiO2) 24.78% and aluminum oxide (Al2O3) 29.60%. The fly ash produced from this fractionation is used as the base material for the synthesis of 4A zeolite. The fly ash is reacted with sodium hydroxide (NaOH) at room temperature, yielding a gel that is subsequently crystallized into 4A zeolite through a reflux process. The resulting zeolite crystals are then supplemented with Al2O3 and disodium dihydrogen ethylenediaminetetraacetate (Na2EDTA) as sources of aluminum to achieve a molar ratio of Si/Al = 1.42. Optimal quality 4A zeolite crystals were obtained from the synthesis of 5.9351 g of medium fraction fly ash, along with 1 g Al2O3, 4 g NaOH, and 0.569 g Na2EDTA. Infrared (IR) characterization results indicate that the optimal 4A zeolite from medium fraction fly ash is characterized by crystals with the addition of 1.5 g of Al2O3. Wide absorption bandwidths are typically caused by large spectral line widths, which can occur if a significant amount of energy is absorbed by various vibrational modes, assuming that excess Al2O3 leads to the formation of functional groups that contribute to the same band. A peak at a wavelength of 564 cm-1 indicates double ring stretching vibrations, while a peak at 661 cm-1 indicates symmetric stretching vibrations of the zeolite framework. Meanwhile, peaks at wavelengths of 3460.86 cm-1 and 974.71 cm-1 indicate detected O-H absorption